FLASH Radiotherapy: History and Future - Lin, Binwei; Gao, Feng; Yang, Yiwei; Wu, Dai; Zhang, Yu; Feng, Gang; Dai, Tangzhi; Du, Xiaobo (Frontiers in Oncology, 2021)
The biological effects of radiation dose to organs at risk surrounding tumor target volumes are a major dose-limiting constraint in radiotherapy. This can mean that the tumor cannot be completely destroyed, and the efficacy of radiotherapy will be decreased. Thus, ways to reduce damage to healthy tissue has always been a topic of particular interest in radiotherapy research. Modern radiotherapy technologies such as helical tomotherapy (HT), intensity-modulated radiation therapy (IMRT), and proton radiotherapy can reduce radiation damage to healthy tissues. Recent outcomes of animal experiments show that FLASH radiotherapy (FLASH-RT) can reduce radiation-induced damage in healthy tissue without decreasing antitumor effectiveness. The very short radiotherapy time compared to that of conventional dose-rate radiotherapy is another advantage of FLASH-RT. The first human patient received FLASH-RT in Switzerland in 2018. FLASH-RT may become one of the main radiotherapy technologies in clinical applications in the future. We summarize the history of the development of FLASH-RT, its mechanisms, its influence on radiotherapy, and its future.